Temperature dependence of liverwort diversification reveals a cool origin and hot hotspots - Karola Maul; S. Robbert Gradstein; Dietmar Quandt; Michael Kessler (Scientific Reports)
Abstract The evolutionary history underlying gradients in species richness is still subject to discussions and understanding the past niche evolution might be crucial in estimating the potential of taxa to adapt to changing environmental conditions. In this study we intend to contribute to elucidation of the evolutionary history of liverwort species richness distributions along elevational gradients at a global scale. For this purpose, we linked a comprehensive data set of genus occurrences on mountains worldwide with a time-calibrated phylogeny of liverworts and estimated mean diversification rates (DivElev) and mean ages (AgeElev) of the respective genera per elevational band. In addition, we reconstructed the ancestral temperature preferences of the genera. We found that diversification rates increase linearly with temperature, and hence decrease with elevation. This pattern is mainly driven by epiphytic genera. In contrast, overall genus age is highest at intermediate elevations where liverwort species richness peaks and decreases towards both ends of the elevational and thermal gradient. Our results further indicate that the ancestral lineages from which the extant liverwort genera descended had a preference for cool and humid habitats. We conclude that the extant liverwort species diversity accumulated over long time under these climatic conditions, which are today prevailing at mid-elevations of the world’s mountains. Subsequently, liverworts expanded their ranges from these temperate areas towards warm (with high diversification rates) and cold regions (with low diversification rates), located in contemporaneous (tropical) lowlands and high mountains, respectively. The conserved preference for temperate climates shared by the majority of liverwort lineages gives reason to the assumption that they will not be able to cope with the conditions induced by rapid climate warming, whereas the current low-elevation radiation may be less affected by climate change.